The colonel and Little Missie Buffalo Bill, Annie Oakley, and the beginnings of superstardom in America - McMurtry, Larry 1936-2021 (Simon & Schuster, 2005)
In this dual biography, McMurtry explores the lives, the legends, and above all the truth about two larger-than-life American figures. With his Wild West show, Buffalo Bill Cody helped invent the image of the West that still exists today--cowboys and Indians, rodeo, rough rides, sheriffs and outlaws, trick shooting, Stetsons, and buck-skin. His most celebrated protégée, the short, slight Annie Oakley--born Phoebe Ann Moses in Ohio--spent sixteen years with Buffalo Bill's Wild West, where she entertained Queen Victoria and Kaiser Wilhelm II, among others. Beloved by all who knew her, Oakley became a legend in her own right, and after her death achieved a new lease of fame in the musical Annie, Get Your Gun. They were cultural icons, setting the path for all that followed.--From publisher description.
Includes bibliographical references (S. 233 - 234) and index
Keywords: Buffalo Bill -- 1846-1917; Oakley, Annie -- 1860-1926; Buffalo Bill's Wild West Company; Entertainers -- United States -- Biography; Shooters of firearms -- United States -- Biography; Scouts and scouting -- West (U.S.) -- Biography; Wild west shows; Wild west show; USA; Biografie